2021
DOI: 10.1007/s00406-021-01287-3
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant effect of repetitive transcranial magnetic stimulation is not impaired by intake of lithium or antiepileptic drugs

Abstract: Introduction The effect of concomitant medication on repetitive transcranial magnetic stimulation (rTMS) outcomes in depression remains understudied. Recent analyses show attenuation of rTMS effects by antipsychotic medication and benzodiazepines, but data on the effects of antiepileptic drugs and lithium used as mood stabilizers or augmenting agents are sparse despite clinical relevance. Preclinical electrophysiological studies suggest relevant impact of the medication on treatment, but this mig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Further, although non-antidepressant concomitant medications were noted in a binary fashion (Table 3), we did not collate more detailed data such as the type of mood stabiliser medication (lithium or anticonvulsant mood stabilisers), concomitant benzodiazepine administration or the doses and treatment durations of these medications. This omission may be of relevance given these medications' possible influences on cortical excitability and therefore rTMS response [88,89], and in view of the literature that emerged since this study's conceptualisation that discuss the impact concomitant benzodiazepines might have on antidepressant response to rTMS [90e92]. Additionally, we did not systematically record tolerability issues expected with rTMS therapy, eg.…”
Section: Discussionmentioning
confidence: 99%
“…Further, although non-antidepressant concomitant medications were noted in a binary fashion (Table 3), we did not collate more detailed data such as the type of mood stabiliser medication (lithium or anticonvulsant mood stabilisers), concomitant benzodiazepine administration or the doses and treatment durations of these medications. This omission may be of relevance given these medications' possible influences on cortical excitability and therefore rTMS response [88,89], and in view of the literature that emerged since this study's conceptualisation that discuss the impact concomitant benzodiazepines might have on antidepressant response to rTMS [90e92]. Additionally, we did not systematically record tolerability issues expected with rTMS therapy, eg.…”
Section: Discussionmentioning
confidence: 99%
“…Increased use of mood stabilizers in the group with bipolar depression was anticipated due to their common use in this patient population. Previous work has shown that intake of these medications aswell as that of lithium is not associated with inferior treatment outcomes in the naturalistic setting, providing evidence against the theoretical concern that drugs with an anticonvulsive mechanism of action might hamper with rTMS effects [20]. The less widespread use of SNRIs in the group of bipolar patients might be associated with concerns of increased risk of inducing mania.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported previously on patients of this cohort with regards to rTMS outcomes, however with a then different and/or smaller samples and different objectives [16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…31 An interpretation of these studies may be that quetiapine blunts the effects of rTMS, such that antipsychotics as a class may act as a moderator toward treatment responsiveness as suggested by others 32 ; meanwhile, mood stabilizers and antiepileptic drugs commonly used in difficult-to-treat mood disorders, including bipolar disorder, are not suggested to impinge on treatment effect of rTMS. 33 Moreover, sequential bilateral rTMS fails to achieve superiority to unilateral treatment, and given the established efficacy unilateral stimulation offers, efforts to optimize unilateral rTMS serve as a useful heuristic platform to begin to build from.…”
Section: Scan Nowmentioning
confidence: 99%